2019
DOI: 10.4028/www.scientific.net/msf.966.83
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Modified SiO<sub>2</sub> on the Hydrophobic Properties as Self-Cleaning Materials

Abstract: In this work, hydrophobic of modified SiO2 coating for self cleaning material were prepared by dip-coating methods and solvothermal manual. SiO2 was successfully prepared from silica sand by purified followed sol-gel methods. Tetraetoxysilane (TEOS) and Hexamethyldisilanze (HMDS) were used as surface chemical modification agents with varied mass of SiO2, which were 1, 2, 3, and 4 g. X-ray fluorescence spectrometer (XRF) , X-ray powder diffraction (XRD), Particle size analyzer (PSA), Ultraviolet–visible spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The contact angle values on the glass samples coated with PDMS/SiO 2 are shown in Table II. Other research has reported that the addition of SiO 2 content to modified SiO 2 material for indium tin oxide (ITO) resulted in changes in the formed contact angle due to surface roughness and low free energy [6]. Therefore, it is evident that the use of PDMS and SiO 2 plays a role in the hydrophobicity of the material in this research.…”
Section: B Hydrophobic Coating Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…The contact angle values on the glass samples coated with PDMS/SiO 2 are shown in Table II. Other research has reported that the addition of SiO 2 content to modified SiO 2 material for indium tin oxide (ITO) resulted in changes in the formed contact angle due to surface roughness and low free energy [6]. Therefore, it is evident that the use of PDMS and SiO 2 plays a role in the hydrophobicity of the material in this research.…”
Section: B Hydrophobic Coating Resultsmentioning
confidence: 64%
“…It is believed that the homogenous particle size of SiO 2 (5 µm) due to the addition of the CTAB compound as an additive to homogenize the particle distribution influenced the formed contact angle. Other research has reported suboptimal contact angle results due to non-homogeneous coating processes and particle sizes (without the addition of a surfac-tant) [6]. The glass substrate used in this research is polar and has a smooth surface, so when the glass surface interacts with water (which is polar), it results in a hydrophilic interaction.…”
Section: B Hydrophobic Coating Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Therefore, it can resist more against corrosive solution. The addition of SiO 2 particles improve coating resistance and quality with micro/nano structure [59–61] . As common anticorrosive coating, PTFE/PTFE/EP primary layer has a good shielding effect and exceptional barrier against corrosive media.…”
Section: Resultsmentioning
confidence: 99%